Retrospective Study of Decubitus Ulcer in Hospitalized Patients - Rosmarwati, Ervina; Mulianto, Nurrachmat (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Decubitus ulcer is an area of necrotic tissue due to compression of protrusion because of prolonged immobilization. Decubitus ulcer is complication that often occur due to prolonged bed rest. Decubitus ulcer can interfere with patient's recovery process and prolonged hospital stay. Purpose: To investigate profile of decubitus ulcer in hospitalized patients in Dr. Moewardi General Hospital Surakarta during 2017- 2020. Methods: This descriptive retrospective study was conducted by using medical record of decubitus ulcers (ICD 10 L89.0, L89.1, L89.2, L89.3) in Dr. Moewardi General Hospital Surakarta during 1st January 2017-31st December 2020. Result: There were 375 decubitus ulcer patients, mostly aged 70 years or more (29.1%) and dominated by women (56%). Patients with decubitus ulcers often hospitalized in the regular ward (75.2%) with the longest length of stay being around 0-10 days (49.6%) and the most common comorbidities was malignancy (20.5%). Systemic antibiotic ceftriaxone was most often given to decubitus ulcer patients (21.6%). Most of the patients with decubitus ulcers had stage 2 decubitus ulcers (53.6%) with a predisposition to the affected area being the sacrum area (33%). The most frequently used therapy for decubitus ulcers was hydrogel dressing (33.9%). Conclusion: Decubitus ulcers are often found in patients over 70 years of age with comorbid malignancies. The most common diagnosis was stage 2 decubitus ulcers, predisposing to the sacral region and the most frequently used therapy was hydrogel dressing with ceftriaxone as a systemic antibiotic.